2021
DOI: 10.3390/life11090905
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 24 h Compression Interventions with Different Garments on Recovery Markers during Running

Abstract: Compression and temperature manipulation are discussed as strategies to improve performance markers and recovery in sports. Here, we investigate the effects of compression stockings made with fabric, either combined or not with heating and cooling substances, on variables related to running performance and recovery. Ten trained runners (mean ± standard deviation age 45 ± 9 years old, body mass 69 ± 7 kg, height 166 ± 4 cm) with no experience of using compression garments performed an intense running session of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
0
0
1
Order By: Relevance
“…The direct measurement of venous haemodynamics in this study affirms the ability of CGs to improve recovery by way of enhanced venous return, though future research could consider how this may influence subsequent performance longer than 5 m in duration. Additionally, Carvalho et al [152] reported no change to mean or maximum skin temperature when compression stockings were worn for 24 h following a race pace treadmill run, though how this may change in hot environments is not known.…”
Section: Physiological Effects During Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…The direct measurement of venous haemodynamics in this study affirms the ability of CGs to improve recovery by way of enhanced venous return, though future research could consider how this may influence subsequent performance longer than 5 m in duration. Additionally, Carvalho et al [152] reported no change to mean or maximum skin temperature when compression stockings were worn for 24 h following a race pace treadmill run, though how this may change in hot environments is not known.…”
Section: Physiological Effects During Recoverymentioning
confidence: 99%
“…The direct measurement of venous haemodynamics in this study affirms the ability of CGs to improve recovery by way of enhanced venous return, though future research could consider how this may influence subsequent performance longer than 5 min in duration. Additionally, Carvalho et al [152] reported no change to mean or maximum skin temperature when compression stockings were worn for 24 h following a race pace treadmill run, though how this may change in hot environments is not known. Decreased heart rate, as well as decreased total peripheral vascular resistance during recovery, was also reported in Piras and Gatta [153] with the use of a custom-made fullbody compression swimsuit for 90 min after a maximal 400 m swim.…”
Section: Physiological Effects During Recoverymentioning
confidence: 99%
“…Carvalho et al 41 relataram nenhuma alteração na temperatura média ou máxima da pele quando meias de compressão foram usadas por 24 horas após uma corrida em esteira, embora não se saiba como isso pode mudar em ambientes quentes.…”
Section: Recuperação Do Desempenho: Resultados Fisiológicos Durante A...unclassified